Siva Nataraja Perspektif Teo-Estetik - Ni Made Evi Kurnia Dewi (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Siva Nataraja is Shiva in the form of dancing. Siva Nataraja is a symbol of the cosmic awareness dance. The Siva Nataraja dance contains very high artistic value and is full of expressions of religiosity. As the master of art, He is called Adiguru or the first art teacher who taught art to gods and mankind. Various mystical movements (mudras) symbolizing the cosmic dance. The Siva Nataraja dance is a combination of the forces of Sekala (Real) and Niskala (Unreal). The essence of the Shiva Nata Raja dance is to guide the soul of every being to realize his divine nature in order to attain the highest awareness of Shiva, as 'sangkan paraning dumadi'.The cosmic dance of Siva Nataraja symbolizes the 5 (five) activities of God called Pancakriya and Panca Aksara (five characters). Pancakriya consists of 1) Srsti (Creation), 2) Shtiti (Maintenance), Samhara (Mengembikan), Tirobhava (Khayal / Illusion), and Anugraha (Gift / Blessing). Panca Aksara is a power that can remove blemishes and sins. Si Wa Ya Na Ma, is a mantra. Si reflects God, Wa is a gift, Yes is the soul, Na is the power that covers the intellect, Ma is the egoism that shackles the soul. The five characters form the body of Shiva and it occurs within each individual soul, at the atomic level. Offerings of beauty or art can be interpreted as an expression of one's devotion to God, In order to attain Siva's cosmic consciousness, the art of devotional service is capable of being a bridge to attaining union with Siva and attaining Samarasya, the pinnacle of aesthetic and mystical experience which culminates in becoming one, namely the highest ananda.